A Review of Hydrogel Application in Wastewater Purification - Lilyan Alsaka; Lina Alsaka; Ali Altaee; Syed Javaid Zaidi; John Zhou; Tayma Kazwini (Separations)
Hydrogels have garnered considerable interest in water purification owing to their distinctive physicochemical characteristics, including high porosity, modifiable surface chemistry, and superior water retention capacity. This paper provides a thorough examination of the use of hydrogels in wastewater treatment. It encompasses their categorization and separation procedures, including size exclusion, adsorption, electrostatic interactions, and non-sieving processes. Furthermore, it examines how functional groups improve the efficiency of pollutant removal. The review examines hydrogel composites and their filtering processes, measuring their efficacy in adsorption and evaluating the benefits and limits of hydrogels, especially regarding regeneration capacities. It explores hydration processes in hydrogels, emphasizing the fundamental mechanisms and measuring methods involved. Future research must prioritize optimizing hydrogel design to enhance mechanical strength and reusability, investigate innovative functionalization techniques to address emergent contaminants, and establish scalable manufacturing methods for extensive industrial use.